Dynamics of Herbivorous Fish and Its Role in Controlling Algal Coverage in Coral Reef Restoration Area Affected by the Bleaching Phenomenon in 2016 - Chair Rani; Abdul Haris; Ahmad Faizal (Jurnal Penelitian Pendidikan IPA, 2023)
Coral reefs in the waters of Liukangloe Island were reported to have experienced a bleaching phenomenon in May 2016 and rehabilitation efforts were carried out in 2019. This study aimed to analyze the structure of the herbivorous fish community and its role in controlling algal cover in the rehabilitation area. Observations of herbivorous fish were carried out using visual census techniques on an area of ​​4m2 and observation of algae in 0.5x0.5 m2 transects on several coral attachment media from dead coral substrates. The results showed that the proportion of herbivorous fish species in the transplant area ranged from 15.81-58.67% and the proportion of individuals ranged from 12.51-34.62%. The dynamics of the number of species and abundance of herbivorous reef fish did not show significant differences between substrates and had the same dynamic pattern in all substrates uses but varied temporally according to the time of observation. The exception is the rubble area which continues to increase until the end of the observation. A high number of herbivorous fish species richness was observed in the branching and natural coral substrates and low in the rubble substrate. The abundance of herbivorous reef fish showed a significant and negative relationship to algal cover and confirmed that the presence of herbivorous reef fish could control or reduce the value of algal cover.